Ulceroglandular form of Тularemia - A. L. Rossina; S. B. Chuelov; A. A. Korsunskiy; O. A. Kaschenko; I. G. Lyubeznova; A. E. Atapina; O. A. Dolgushina; A V. Tebenkov; O. V. Shamsheva (Детские инфекции (Москва), 2019)
The article provides a brief literature review on tularemia, shows the current epidemic situation of tularemia in Russia and analyzes the characteristic clinical picture of the ulceroglandular form of tularemia. A clinical example of an ulceroglandular form of tularemia in a child.